Health Economics Perspective on Indonesian Telemedicine Platform Practices: A Qualitative Study - Wibowo, Yossico Ria; Pasaribu, Rina Djunita (UI Scholars Hub, 2025)
Telemedicine in Indonesia has experienced significant growth since its introduction in 2014. The financing system is regulated independently by each platform, leading to disparities in teleconsultation fees and medical incentives. This qualitative study, which involved a literature review and interviews with 33 participants, offered a health economics perspective on the implementation of telemedicine. The recommended teleconsultation fee ranges from USD 0.05 to USD 2.54, with medical incentives set at USD 1,59-3.18 for general practitioners and USD 4.77-6.36 for specialists, using telephone or video calls as the preferred means of teleconsultation. Although most patients and Indonesian Medical Association administrators generally agreed with these recommendations, platform managers expressed reservations, particularly regarding the fees for specialists. Video calls were widely accepted as the preferred medium for teleconsultations. This study concludes that the maximum recommended teleconsultation fee is USD 2.54, with minimum medical incentives of USD 1.59 for general practitioners and USD 4.77 for specialists, and that the teleconsultation medium for making a diagnosis on the telemedicine platform is chat, with a mandatory feature allowing optional use of video calls, which can be used according to the mutual agreement and adjustment of teleconsultation fees.